Cell Therapy as an Alternative approach for COVID-19 Infection Consequences: A Non-Systematic Review - Hoda Elkhenany; Shilpi Gupta; Mostafa F. Abdelhai (International Journal of Coronaviruses, 2021)
The current uncontrollable outbreak of novel coronavirus (COVID-19) has unleashed severe global consequences in all aspects of life and society, bringing the whole world to a complete halt and has modeled significant threats to the global economy. The COVID-19 infection manifests with flu-like symptoms such as cough, cold, and fever resulting in acute respiratory distress syndrome (ARDS), lung dysfunction, and other systemic complications in critical patients are creating panic across the globe. However, the licensed vaccine has started to show up; some resulted in side effects that would limit its possibility in some circumstances as allergic personnel, for example. Moreover, the production and approval of new drugs is a very complicated process and takes a long time. On the other hand, stem cells have gone the extra mile and intensively investigated at preclinical and clinical studies in various degenerative diseases, including infectious ones. Stem cells are proposed as a broad-spectrum therapeutic agent, which may suppress the exaggerated immune response and promote endogenous repair by enhancing COVID-19 infected lung microenvironment. Also, stem cells have different application manners, either direct transplantation, exosome transplantation, or drug delivery of specific cytokines or nanoparticles with antiviral property by engineering stem cells. This review discusses and summarizes the possible emerging role of cell-based therapy, especially stem cell therapy, as an alternative promising therapeutic option for the treatment and control of novel COVID-19 and its potential role in tissue rejuvenation after COVID-19 infection.
Keywords: SARS-CoV-2